EFFECTS OF DEFOLIANTS ON TECHNOLOGICAL QUALITY AND CHICKEN OIL AND NUCLEAR OUTPUT OF COTTON CULTIVATED IN WEAKLY DEGRADED AREAS - Uljaboev Alijon Abdullajonovich; Komilova Nafosat Alimardon qizi; To‘xtasinov Muxammadyusuf Dilmurodjon o‘g‘li (Web of Journals Publishing, 2024)
The technological indicator of cotton fiber, chicken oil, and the effects of defoliants on nuclear output in questioning the growth and development of the S-8290 grain variety, which is being cared for in the weakly salted soils of the province of Anchorage.
Keywords: Weak saline field, UzDEF and PolyDEF defoliants, S-8290 grain variety, cotton fiber, oil in the chicken nucleus.